Health Education on Perimenopause and Menopause for Indonesian Migrant Workers in South Korea - Vivi Silawati; Damayanti, Ivanda Eka; Asya Nawar Karimah; Nurahayu, Siti; nabilah; kristiningrum, dian; sugiharti, novi; samsiah, Nur; purnawati, neneng santi; megawati (International Journal of Community Services, 2026)
This community service program aimed to improve knowledge and awareness of perimenopause and menopause among Indonesian migrant women in South Korea. Many Indonesian female workers face unique challenges related to hormonal changes, limited health access, and low reproductive health literacy. The activity was conducted at Rumah Indonesia Seoul (RUMAISA) through interactive counseling, bilingual educational materials, and relaxation practice sessions. A total of 35 participants attended the session, which included pre-test and post-test evaluations. The results showed a significant increase in participants’ understanding of hormonal changes, menopause management, and healthy lifestyle practices. This program demonstrates that culturally sensitive, bilingual health education can effectively enhance reproductive health awareness and support the well-being of migrant women.